Surfactin alleviated hyperglycaemia in mice with type 2 diabetes induced by a high-fat diet and streptozotocin - Xiaoyu Chen; Hongyuan Zhao; Fanqiang Meng; Libang Zhou; Zhaoxin Lu; Yingjian Lu (Food Science and Human Wellness)
Type 2 diabetes mellitus (T2DM) is associated with liver dysfunction and intestinal dysbiosis. Bioactive peptides (BAPs) have been reported to ameliorate T2DM by preventing oxidative damage to the liver. Bacillus amyloliquefaciens fmb50 produces the lipopeptide surfactin with a wide range of biological activities. The effects of surfactin on T2DM, on the other hand, have not been studied. In the present study, 80 mg/kg body weight surfactin supplementation lowered fasting blood glucose (FBG) levels by 21.05 % and insulin resistance (IR) by 18.18 % compared with those in the T2DM group, reduced inflammation, and increased antioxidant activity in mice with T2DM induced by a high-fat diet (HFD) and streptozotocin (STZ). According to further research, surfactin administration reduced Firmicutes-to-Bacteroidetes ratios while increasing Bifidobacterium abundance by 20 times and the level of the tight junction protein Occludin by 18.38 % and ZO-1 by 66.60 %. Furthermore, surfactin also improved hepatic glucose metabolism by activating the adenosine monophosphate-activated protein kinase (AMPK) signalling pathway, increasing glycogen synthesis and glucose transporter 2 (GLUT2) protein expression while reducing glucose-6-phosphatase (G6Pase) protein expression. In addition, the increased Bifidobacterium abundance indirectly reduced the liver burden of the metabolic products indole, cresol and amine produced by saprophytic bacteria. All of these findings revealed that surfactin not only ameliorated HFD/STZ-induced gut dysbiosis and preserved intestinal barrier integrity but also enhanced hepatic glucose metabolism and detoxification function in T2DM mice. The gut microbiota appeared to be important in controlling glucose metabolism, IR, fat accumulation, inflammation and antioxidation, according to Spearman’s correlation coefficients. All data indicated that surfactin alleviated hyperglycaemia in mice with T2DM induced by HFD/STZ.